Hubungan Antara Regulasi Diri dengan Disiplin Belajar Pada Siswa SMK Negeri 2 Kota Banda Aceh - Rudiansyah, Ibnu; Bakar, Abu; Bustamam, Nurbaity (Jurnal Suloh, 2024)
Children who have high self-regulation will be diligent in learning and continue to learn continuously without knowing despair and can put aside things that can interfere with learning activities. Self-regulation is the process of directing individuals to be able to control themselves against negative impulses from the environment. This study aims to find out the overview of self-regulation and student learning discipline, as well as to find out the relationship between self-regulation and learning discipline in students of SMK Negeri 2 Banda Aceh City. The total population in this study is 641 students consisting of grades 10 and 11 of SMK Negeri 2 Banda Aceh. This study uses a quantitative approach with a descriptive type of quantitative research. The sampling technique uses the Multistage random sampling technique, so that the number of research samples is 100 students. The data analysis technique in this study uses descriptive statistical analysis and correlation analysis. There are five categorizations, namely Very High, High, Medium, Low and Very Low. Based on statistical analysis, the level of self-regulation and learning discipline of dominant students is in the low category. Based on correlation analysis, it is known that the correlation value between self-regulation variables and learning disciplines has a value of 0.422** and a significance value of 0.000, meaning that there is a positive and significant correlation between self-regulation and learning discipline, with correlations that are at a moderate level.